Effects of Renal Denervation on Ambulatory Blood Pressure Measurements in Patients With Resistant Arterial Hypertension. Issue 5 (2nd April 2014) - Lambert, Thomas; Blessberger, Hermann; Gammer, Verena; Nahler, Alexander; Grund, Michael; Kerschner, Klaus; Buchmayr, Gunda; Saleh, Karim; Kammler, Jürgen; Steinwender, Clemens
Abstract Background The sympathetic nervous system is an important factor in hypertension. In patients suffering from resistant hypertension, transfemoral renal sympathetic denervation (RDN) reduces office blood pressure (BP) values. Hypothesis Ambulatory BP measurement (ABPM) is a better predictor than office BP of cardiovascular morbidity and mortality. We thus believe that ABPM should be added to the systematic evaluation and follow‐up protocol when treating patients with resistant hypertension with RDN. Therefore, we evaluated the effect of RDN on mean 24‐hour BP by the use of ABPM. Methods Patients with resistant hypertension (office systolic BP >160 mm Hg, or >150 mm Hg in patients with diabetes) have been treated with RDN. Ambulatory BP measurement was performed at baseline and at 3 and 6 months after RDN. Patients with a 24‐hour systolic BP reduction of ≥5 mm Hg were classified as responders. Results Of 86 patients initially enrolled in the study, 5 had to be excluded from the analysis because of <70% valid ABPM recordings. Out of the 81 studied patients, we found 49 responders (60.5%). In all patients, office BP decreased from 169.9/87.8 mm Hg to 153.5/86.3 mm Hg (P < 0.001/P = not significant [NS]) and 24‐hour BP decreased from 144.3/86.0 mm Hg to 139.9/84.0 mm Hg (P = 0.025/P = NS) 6 months after RDN. In responders, office BP decreased from 169.6/90.3 mm Hg to 143.7/79.7 mm Hg (P < 0.001/P < 0.001). The ABPM levels started at 144.3/84.7 mm Hg and decreased to 138.3/81.5 mm Hg (P = 0.025/P = 0.045). In nonresponders, office BP was 150.2/84.0 mm Hg and 24‐hour BP was 144.5/84.7 mm Hg at baseline; at 6 months, office BP was 168.7/96.4 mm Hg (P < 0.001/P = NS) and 24‐hour BP was 142.2/81.5 mm Hg (P = NS/P = NS). Conclusions Office BP and AMBP levels can be significantly lowered by RDN in patients with resistant hypertension.